2017
DOI: 10.4269/ajtmh.16-0941
|View full text |Cite
|
Sign up to set email alerts
|

Building and Rebuilding: The National Public Health Laboratory Systems and Services Before and After the Earthquake and Cholera Epidemic, Haiti, 2009–2015

Abstract: Abstract.Before the 2010 devastating earthquake and cholera outbreak, Haiti’s public health laboratory systems were weak and services were limited. There was no national laboratory strategic plan and only minimal coordination across the laboratory network. Laboratory capacity was further weakened by the destruction of over 25 laboratories and testing sites at the departmental and peripheral levels and the loss of life among the laboratory health-care workers. However, since 2010, tremendous progress has been m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Although the laboratory capacity in Haiti has increased dramatically since the 2010 earthquake and cholera outbreak, the main areas strengthened have been molecular testing for TB, HIV, malaria and diarrhoeal and respiratory diseases. 23 Access to quality microbiological diagnostics is still limited, and the guided use of antibiotics through microbiological results and the surveillance of ABR in the country is minimal. Boulos et al 24 reported that not having access to microbiological culture was associated with increased fatality among neonatal sepsis cases in Haiti.…”
Section: Discussionmentioning
confidence: 99%
“…Although the laboratory capacity in Haiti has increased dramatically since the 2010 earthquake and cholera outbreak, the main areas strengthened have been molecular testing for TB, HIV, malaria and diarrhoeal and respiratory diseases. 23 Access to quality microbiological diagnostics is still limited, and the guided use of antibiotics through microbiological results and the surveillance of ABR in the country is minimal. Boulos et al 24 reported that not having access to microbiological culture was associated with increased fatality among neonatal sepsis cases in Haiti.…”
Section: Discussionmentioning
confidence: 99%
“…These efforts proved fruitful: by 2015, Haiti moved from being ranked the fourth-worst performing country in the Latin American and Caribbean region to the sixth-best in terms of investigating suspected cases of measles and rubella [ 51 ]. However, governance and funding challenges continued to undermine surveillance efforts [ 51 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…The Haitian national laboratory network has grown and improved significantly with the support of PEPFAR. Hospital laboratories were either built or renovated, and the number of facilities with access to automated chemistry, haematology and tuberculosis (GeneXpert) testing tripled after the 2010 earthquake 8. The Global Heath Security Agenda (GHSA) offers another opportunity to strengthen the Haitian laboratory system to support infectious diseases surveillance and outbreaks response.…”
Section: Opportunities To Improve Hiv Rapid Test Quality Management Smentioning
confidence: 99%
“…LNSP is at the top of the pyramid and serves as a reference laboratory, overseeing and coordinating the activities at the three levels of services. Three regional laboratories are located at teaching hospitals where a comprehensive range of laboratory services are provided and seven laboratories located at departmental hospitals constitute the third and second tier, respectively 8. About 240 primary level, peripheral public healthcare facilities/laboratories form the bottom of the pyramid, where basic laboratory tests are performed.…”
Section: Introductionmentioning
confidence: 99%